Management compensation and firm-level income inequality - Anders Frederiksen; Odile Poulsen (Institute for the Study of Labor (IZA), 2008)
In recent decades, most developed countries have experienced a simultaneous increase in income inequality and management compensation. In this paper, we study the relation between management compensation and firm-level income dynamics in a general equilibrium model. Empirical estimation, of the model's key parameters show that the rising management premium is indeed the main driving force behind the observed increase in income inequality. This is the case even when other potential sources such as technological progress and skill-biased technological change are taken into account. We also show that a rising management premium produces income distribution dynamics at the firm level which are similar to those observed at the market level, i.e. rising income inequality overall as well as within and between education groups.
urn:nbn:de:101:1-2008092349
Keywords: J3; 330; Income inequality; two-sector search model; skill-biased technological change; personnel data; Lohnstruktur; Unternehmen; Führungskräfte; Gehalt; Einkommensverteilung; Qualifikation; Technischer Fortschritt; Mehr-Sektoren-Modell; Allgemeines Gleichgewicht; Theorie; Dänemark